Digging up dinosaurs - Aliki (New York : HarperCollins, 1988)
Briefly introduces various types of dinosaurs, explaining how scientists find, preserve, and reassemble the giant dinosaur skeletons seen in museums.
Keywords: Dinosaurs; Fossils